(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The excavation of a rural settlement near Lleida has allowed the recovery of an important ceramic context dating from the end of the first century to the beginning of the second century AD. The deposit includes a broad representation of terra sigillata and culinary ware of the period, usually with few signs of use. However, the interest of the repertoire resides in the diversity and quantity of the conserved grafitti. The texts were written almost exclusively in Latin, but include some example in Greek. Its content is limited to onomastic representations (in Latin, Greek and native), although indications of property and insulting or jocular expressions are also identified. This article analyzes one of the fragments, belonging to a jug in common ware (a characteristic production of the High Empire in the territory), which seems to retain an Iberian onomastic indication and maybe a theonym. This hypothesis would confer a votive character to the inscription. The composition and chronology of the deposit, coming from a settlement located on the periphery of a Roman municipium, allows us to make some considerations about the evolution of the native onomastics in imperial times, as well as on the cultural and religious context in which this onomastic is inserted.